Endometrial microbiota profile in in-vitro fertilization (IVF) patients by culturomics-based analysis - Cariati, Federica; Carotenuto, Consolata; Bagnulo, Francesca; Pacella, Daniela; Marrone, Vincenzo; Paolillo, Rossella; Catania, Maria Rosaria; Di Girolamo, Raffaella; Conforti, Alessandro; Strina, Ida; Alviggi, Carlo (Frontiers in Endocrinology, 2023)
Introduction It is well recognized that the human uterus and adjoining tissues of the female reproductive tract exist in a non-sterile state where dysbiosis can impact reproductive outcomes. The endometrial microbiota is a part of this greater milieu. To date, it has largely been studied using 16S rRNA or metagenomics-based methodologies. Despite the known advantages of sequencing analysis, several difficulties have been noted including sample contamination and standardization of DNA extraction or sequencing. The aim of this study was to use a culturomics-based method to analyze the endometrial microbiota and correlate the results with ongoing pregnancy rates. Methods A prospective cohort study was performed at the University of Naples from June 2022 to December 2022. Ninety-three patients undergoing an IVF cycle with single embryo transfer (ET) (fresh or frozen) were enrolled in the study. Following ET, the catheter tip was inserted into brain heart infusion (BHI) medium under sterile conditions for culture. After 24h and 48h of incubation the microorganisms in the colonies were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Results Overall, 68 (73,92%) patients resulted positive for one or more microbes and 24 patients (26,08%) had no microbial growth. Across all participants, the four most important phyla were Firmicutes (87,76%), Proteobacteria (27,94%), Actinobacteria (10,29%) and Ascomycota (8,82%). Lactobacillus species, in particular, was significantly correlated with ongoing pregnancy rate (p=0,05). On the other hand, Staphylococcus subspecies (spp.) (p<0,05) and Enterobacteriaceae (p<0,001) were found to have a negative impact on the implantation rate. Discussion Detection of bacteria by culturomics from catheter tips used for embryo transfer has been shown to be a reliable method to detect pathogen growth. Endometrial microbiota testing in clinical practice could certainly offer a means to further improve diagnosis and treatment strategies in IVF patients.